Phylogenetic relationships of Asian freshwater Mytiloidea (Bivalvia): a morphological and genetic comparison of Sinomytilus harmandi, Limnoperna fortunei and Septifer bilocularis. (2nd April 2020) - Morton, Brian; Leung, Priscilla T.Y.; Wei, Jiehong; Lee, Gabriel Y.
ABSTRACT: The Mekong River endemic Sinomytilus harmandi possesses an internal anterior shell septum. It is thus superficially similar to the marine representatives of the, as currently defined, Septiferinae (Mytilidae) although species of the latter possess an anterior adductor muscle located between their septa and are characterised by accessory posterior adductor muscles, both of which are absent in S. harmandi . This study demonstrates that S. harmandi is monophyletic with the only other, similarly native Asian, freshwater mytiloid, Limnoperna fortunei, based on the phylogenetic tree herein presented. Asian freshwaters thus seem to have been colonised by the Mytilidae relatively recently and on two occasions from a common ancestor also associated with representatives of the Lithophaginae, as currently defined. The common presence of an anterior septum in S. harmandi and species of the Septiferinae, as currently recognised, is thus the result of convergence as is the anatomical similarity between S. harmandi and representatives of the Central European Dreissenidae (Heterodonta), which also possess an anterior shell septum.